Changes in incidence rates of outcomes of interest in vaccine safety studies during the COVID-19 pandemic. Issue 23 (20th May 2022) - Xu, Stanley; Hong, Vennis; Sy, Lina S.; Glenn, Sungching C.; Ryan, Denison S.; Morrissette, Kerresa L.; Nelson, Jennifer C.; Hambidge, Simon J.; Crane, Bradley; Zerbo, Ousseny; DeSilva, Malini B.; Glanz, Jason M.; et al.
Highlights: Incidence rates of acute disseminated encephalomyelitis, EMEM, and TTP did not change significantly during the pandemic. Rates of AMI, anaphylaxis, appendicitis, Bell's palsy, convulsion/seizure, GBS, ITP, narcolepsy, stroke and VTE decreased. Rates of Bell's palsy, ITP and narcolepsy were higher in all settings than in in-person settings during the pandemic. Future vaccine safety studies should consider including telehealth visits to identify Bell's palsy, ITP and narcolepsy. Abstract: Background: The COVID-19 pandemic caused an abrupt drop in in-person health care (inpatient, Emergency Department, outpatient) and an increase in telehealth care, which poses challenges in vaccine safety studies that identify outcomes from in-person encounters. We examined the changes in incidence rates of selected encounter-based outcomes during the COVID-19 pandemic. Methods: We assembled a cohort of members from 8 Vaccine Safety Datalink sites from January 1, 2017 through December 31, 2020. Using ICD-10 diagnosis codes or laboratory criteria, we identified 21 incident outcomes in traditional in-person settings and all settings. We defined 4 periods in 2020: January-February (pre-pandemic), April-June (early pandemic), July-September (middle pandemic), and October-December (late pandemic). We defined four corresponding periods in each year during 2017–2019. We calculated incidence rates, conducted difference in difference (DiD) analyses, and reported ratios of incidence rate ratios (RRR) to examine changes in rates from pre-pandemic to early, middle, and late pandemic in 2020, after adjusting for changes across similar periods in 2017–2019. Results: Among > 10 million members, regardless of setting and after adjusting for changes during 2017–2019, we found that incidence rates of acute disseminated encephalomyelitis, encephalitis/myelitis/encephalomyelitis/meningoencephalitis, and thrombotic thrombocytopenic purpura did not significantly change from the pre-pandemic to early, middle or late pandemic periods (p-values ≥ 0.05). Incidence rates decreased from the pre-pandemic to early pandemic period during 2020 for acute myocardial infarction, anaphylaxis, appendicitis, Bell's palsy, convulsions/seizures, Guillain-Barré syndrome, immune thrombocytopenia (ITP), narcolepsy/cataplexy, hemorrhagic stroke, ischemic stroke, and venous thromboembolism (p-values < 0.05). Incidence rates of Bell's palsy, ITP, and narcolepsy/cataplexy were higher in all settings than in traditional in-person settings during the three pandemic periods (p-values < 0.05). Conclusion: Rates of some clinical outcomes during the pandemic changed and should not be used as historical background rates in vaccine safety studies. Inclusion of telehealth visits should be considered for vaccine studies involving Bell's palsy, ITP, and narcolepsy/cataplexy.